ANALISIS PENYIMPANAN VAKSIN DI PUSKESMAS KEDIRI I KABUPATEN TABANAN - Listiani, Putu Ayu Ratih; Putu Ika Indah Indraswari; Ziyyan Silfia Haani (Journal Pharmactive, 2025)
Vaccines are biological products that stimulate the body's immunity and are very susceptible to damage, so they require special handling to maintain their quality. One of them is that proper storage of vaccines is very important because this can have an impact on its potency. This study aims to evaluate the effectiveness of vaccine storage at the Kediri 1 Tabanan Community Health Center using three main indicators: facilities and infrastructure, condition of the refrigerator, and vaccine storage system. Descriptive observational research with a semi-quantitative study design is the methodology employed. The analysis's findings indicate that the facilities and infrastructure indicators scored 81.81%, placing them in the good category. With a percentage of 87.5%, the refrigerator condition indicator is also in the good range. Aside from that, the indicators of the vaccine storage system performed well, with an 85.71% percentage. In summary, the Kediri 1 Tabanan Community Health Center's overall vaccination storage falls within the "good" category. Despite the fact that there is still room for advancement to achieve complete vaccine storage optimization